Analisis Sadd Adz-Dzari’ah Terhadap Praktik Jual Beli Sepeda Motor Bekas Tanpa Surat: Studi Kasus Kabupaten Mandailing Natal Sumatera Utara - Sahrul Gunawan (JOM, 2024)
The phenomenon of buying and selling used motorcycles without complete legal documentation has become increasingly prevalent in Mompang Jae Village, Panyabungan Utara District, Mandailing Natal Regency. This practice raises significant legal and social concerns, particularly regarding its compliance with Islamic legal principles and potential societal impacts. This study seeks to analyze the validity of such transactions through the framework of Sadd Adz-Dzari’ah, an Islamic legal method aimed at preventing actions that may lead to harm (mafsadah). Furthermore, the research investigates the underlying factors driving the persistence of this practice within the community, despite its apparent risks and ethical implications. By employing an empirical legal approach, integrating a living case study and conceptual analysis, this research collects qualitative data from interviews with 10 informants, including buyers, sellers, and relevant authorities. The findings demonstrate that transactions involving undocumented motorcycles are classified as prohibited (haram) under the Sadd Adz-Dzari’ah principle due to the predominance of potential harms over benefits (maslahat). These harms include financial vulnerability, administrative hurdles, and risks of legal disputes or criminal involvement. In light of these findings, this study recommends proactive measures by authorities to curb such practices and emphasizes the importance of public awareness campaigns to educate the community on the legal and social risks posed by undocumented vehicle transactions. This research contributes to the discourse on Islamic legal compliance and offers practical solutions to address emerging socio-legal challenges in contemporary society.